جريمتي تعاطي وترويج المخدرات في التشريع الجزائري - بوراس, طارق; يوسفي, بلقاسم; محامدية, بولعراس (University of Eloued جامعة الوادي, 2023)
تعد جريمتي تعاطي وترويج المخدرات من أبشع الجرائم وأكثرها انتشارا في وقتنا الحالي والتي تمس طاقات الشباب بصفة خاصة والإستقرار الداخلي للبلاد وصورتها في الخارج بصفة عامة فبالنسبة لجريمة تعاطي المخدرات تتخذ العديد من الصور منها التعاطي التجريبي والعرضي والكثيف والمنظم، أما آثارها فتمس الجناب الصحي والنفسي والإجتماعي وحتى الإقتصادي، إذ ترتكز على أركان الجريمة العادية من ركن شرعي ومعنوي ومادي، وتتولد منها العديد من الجرائم كالسرقة والاغتصاب والجرائم المتعلقة بالمرور. أما جريمة ترويج المخدرات فتهدف إلى إقناع المستهلكين بشتى الطرق والوسائل بتعريفهم بنوع السلعة وتأثيراتها مما يؤدي إلى إشباع حاجاتهم ورغباتهم، وتقوم هي الأخرى على نفس الأركان التي تقوم عليها جريمة التعاطي، وتتولد منها العديد منالجرائم لعل أكثرها انتشارا يتمثل في تبييض الأموال وتمويل الإرهاب. وفيما يخص آلياتمكافحةجريمتيتعاطيوترويجالمخدراتفقد انتهجهاالمشرعالجزائريبسنهالقانون 04-18 المتعلقبالوقايةمن المخدراتوالمؤثراتالعقليةوقمعالإستعمالوالإتجارغيرالمشروعينبها، والذي اتسم بالصرامةوتشديدالعقوبة في حق هاتين الجريمتين، بالإضافة إلى القانون 85-05 المتعلقبحمايةالصحةوترقيتها المعدل والمتمم، هذا فضلا على انخراطه الدولي في العديد من الإتفاقيات والوثائق منها الإتفاقية الوحيدة للمخدرات عام 1961، والمنظمة العالمية للصحة، واليونسكو، بالإضافة إلى منظمة الأغذية والزراعة، الإتفاقية الجزائرية الإيطالية لعام 1999، والفرنسة لعام 2003، ومكتب الأمم المتحدة المعني بالمخدرات، ومنظمة الشرطة الدولية الجنائية (الأنتربول)، ومنظمة الجمارك العالمية (مجلس التعاون الجمركي) كما أحدث المشرع الديوان الوطني لمكافحة المخدرات بالجزائر وإدمانها لمكافحة التعاطي وإشراك المجتمع المدني.crimes of drug use and promotion are among the most heinous and most prevalent crimes in our time, which affect the energies of young people in particular and the internal stability of the country and its image abroad in general As for the crime of drug abuse, it takes many forms, including experimental, accidental, intense, and organized abuse. As for its effects, it affects the health, psychological, social, and even economic aspects, as it is based on the pillars of ordinary crime from the legal, moral and material pillars, and many crimes such as theft, rape and traffic-related crimes are generated from it. As for the crime of drug promotion, it aims to convince consumers in various ways and means by introducing them to the type of commodity and its effects, which leads to the satisfaction of their needs and desires. It is also based on the same pillars on which the crime of abuse is based, and many crimes are generated from it, perhaps the most widespread of which is money laundering and terrorism financing. With regard to the mechanisms of combating the crimes of drug use and promotion, the Algerian legislator pursued them by enacting Law No.: 04-18 relating to the prevention of narcotics and psychotropic substances and the suppression of their illicit use and trafficking, which was characterized by strictness and severe punishment for these two crimes, in addition to Law No.: 85-05 on health protection and promotion, amended and supplemented, in addition to its international involvement in many agreements and documents, including the Single Convention on Narcotic Drugs of 1961, the World Health Organization, UNESCO, in addition to the Food and Agriculture Organization, the Algerian-Italian agreement of 1999, France of 2003, and the United Nations Office on Drugs, the International Criminal Police Organization (Interpol), the World Customs Organization (Customs Cooperation Council) The legislator also created the National Office for Combating Drugs and Drug Addiction in Algeria to combat drug abuse and involve civil society.
مذكرة ماستر
Keywords: الجريمة، تعاطي المخدرات، ترويج المخدرات، المكافحة; Crime, drug abuse, drug dealing, combating